High dose of dietary vitamin D3 modulated the yellow catfish (Pelteobagrus fulvidraco) splenic innate immune response after Edwardsiella ictaluri infection. Issue 100 (May 2020) - Cheng, Ke; Tang, Qin; Guo, Xun; Karow, Niel A.; Wang, Chunfang
Abstract: Vitamin D3 (VD3 ) has been shown to modulate the innate immune response in mammals but this has been rarely reported in fish. The current study found that increasing dietary VD3 content can reduce the density of yellow to dark brown pigmented macrophage aggregates (PMAs) in the spleens of yellow catfish infected with Edwardsiella ictaluri . The results of next-generation sequencing showed that a high dose of dietary VD3 (16, 600 IU/kg) mainly affected the splenic immune response during Edwardsiella ictaluri infection via negative regulation of 'NF-κΒ transcription factor activity', 'NIK/NF-κΒ signaling' and the 'i-kappab kinase/NF-κΒ signaling' pathways. Follow-up qPCR showed that dietary VD3 increased the expression of NF-κΒ inhibitor iκb-α, decreased the expression of nf-κb p65, il-6, il1-β and tnf-α, and down-regulated the expression of nik, ikks and nf-κb p52 in the NIK/NF-kappaB signaling pathway. The above results indicate that dietary VD3 can modulate the splenic innate immune response of yellow catfish after Edwardsiella ictaluri infection by inhibiting the NF-κB activation signaling pathways. Graphical abstract: Image 1 Highlights: 16, 600 IU/kg VD3 protected fish spleen from damage caused by E. ictaluri infection. Increasing VD3 reduced the density of pigmented macrophage aggregates in spleen. VD3 affected splenic immune response by inhibiting NF-κB activation signaling pathway.